Display Metrology and Image Quality are Relevant, Vital for Development. Issue 5 (1st September 2018) - Fiske, Tom
Abstract : Display Week 2018 featured a variety of exhibits, seminars, and symposia on topics related to display metrology and image quality. These topics are (or should be) of interest to anyone who's serious about developing displays or integrating displays into a system where visual performance is of paramount concern.